Adsorption study on the removal of copper ions from aqueos solution using sodium hydroxide-modified Carica papaya peels - Shuhaimen, Muhammad Shahrain; Abdullah, Erna Normaya; Mohd Salim, Rosliza; Abu Samah, Mohd Armi; Omar, Muhammad Nor; Ahmad, Mohammad Norazmi (Malaysian Analytical Sciences Society, 2019)
Recently, environment contamination by heavy metals has gained much attention due to the significant impact on public health.Heavy metals such as copper are non-biodegradable pollutants and they are very difficult to eliminate naturally from the environment. Therefore, this study was conducted to deal with the removal copper from an aqueous solution using a highly efficient, environmentally friendly adsorbent from Carica papayapeels (CPP) prepared by chemical treatment of NaOH modification. The effects ofadsorbent mass, pH of the aqueous solution, and contact time were studied in batch experiments. The optimum parameters for the removal of copper (79%) are 0.9 g, pH = 3, and 45 minutes. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR) were employed to validate the efficiencies of the adsorbents towards copper. FT-IR analysis showed that carboxyl and hydroxyl functional groups were involved in the adsorption of copper ions. As a conclusion, the chemical-treated CPP can be utilized as a potential biosorbent for copper removal from aqueous solutions